KEANEKARAGAMAN DAN KELIMPAHAN ASTEROIDEA DI ZONA INTERTIDAL GUSUNG SAPA SEGAJAH KOTA BONTANG - Aditya Irawan; Syawalani, Afsanti; Sari, Lily Inderia (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, Mulawarman University, 2024)
Asteroidea is a class of the phylum Echinodermata which has a radially symmetrical body shape and has five or more arms. The intertidal zone is a coastal area that lies between the highest tides and lowest ebb, this area represents the transition from ocean conditions to land conditions. The purpose of this study was to determine the diversity and abundance of asteroids in Sapa Segajah, Bontang City. This research was conducted in April 2021. Sampling of asteroids using the purposive sampling method was carried out using transect plots measuring 1x1 m2 systematically along the intertidal zone in 12 plots. The results of the study found 3 types of asteroidea species, namely Protoreaster nodosus, Archaster typhicus and Culcita novaeguineae. Asteroidea diversity is in the low criterion with a value of 0.23, uniformity tends to be small or unstable and Protoreaster Nodosus dominates.